When cultural political economy meets 'charismatic carbon' marketing: A gender-sensitive view on the limitations of Gold Standard cookstove offset projects. (September 2019) - Lehmann, Ina
Abstract: Charismatic carbon projects are becoming increasingly popular in the voluntary carbon market. These are carbon offset projects that lend themselves to telling stories about the livelihood benefits they provide for poor people in the Global South in addition to carbon emission savings. I use cultural political economy as a theoretical heuristic to analyse how Gold Standard-certified cookstove carbon offsets are framed as delivering charismatic carbon. Methodologically, this is done through a content analysis of the online visual and textual marketing of 22 Gold Standard-certified cookstove carbon offset projects. I find that the project marketing makes particularly strong claims to improve family livelihoods, income generation and women empowerment, whilst de-politicising the feminist concern with women's agency. The Gold Standard is one of the major and most well-regarded offsetting standards. Therefore, this research may reveal important limitations in the current and future shape of the wider voluntary carbon market.